Identification of psoralen loaded PLGA microspheres in rat skin by light microscopy - Gomes, Anderson J.; Lunardi, Claure N.; Lunardi, Laurelucia O.; Pitol, Dimitrius L.; Machado, Antonio Eduardo H. (Pergamon-Elsevier B.V. Ltd, 2008)
Drug delivery systems involving the use of polymers are widely studied and discovery of biocompatible polymers has become the focus of research in this area. Psoralen loaded poly(DL-lactide-co-glycolide) (PLGA) microspheres to be used in PUVA therapy (psoralen and UVA irradiation (ultraviolet A, 320-400 nm) of psoriasis were identified in paraffin sections by histological analysis. The psoralen loaded PLGA microspheres were prepared using the solvent evaporation technique. They were spherical and possessed an external smooth surface as observed by scanning electron microscopy (SEM) analysis. This study describes a modification in the routine preparation of microsphere samples for examination by light microscopy. The changes involved fixative agents and/or stains allowing the identification of microspheres containing a non-fluorescent material. The preservation and identification of microspheres in tissues for histological processing in paraffin was greatly improved by these modifications as proven by our results. (c) 2007 Elsevicr Ltd. All rights reserved.
Keywords: drug delivery; light microscopy; microspheres; PLGA; psoralen; rat skin; irradiation; stain